The technique of the eggbeater kick - Alexander, M.; Taylor, C.
An important skill in synchronized swimming and water polo, that is used by the players to keep them afloat in an upright position while performing other skills. The skill consists of alternating circular movements of the legs that produce an upward force by the water on the swimmer in order to keep the swimmer afloat in a vertical position. The legs appear to move in a circular pattern, almost like alternating circumduction of the hips accompanied by knee flexion/extension and medial to lateral rotation. The legs move in alternate circular directions during the kick- the right leg moves counterclockwise and the left leg moves clockwise (Sanders 2005). The path of the feet traces an elongated oval during the kick (Figure 7). When one leg is in the recovery phase, the other leg is in the power phase. All the joints of the lower limb are active during the eggbeater kick: the hips, knees, ankles and the subtalar joints of the foot. The joint movements increase in linear velocity from proximal to distal joints, with the fastest linear movements occurring in the foot. The faster the movements of the feet, the greater the propulsive forces on the swimmer. It has been reported that the height maintained in the eggbeater kick is strongly related to foot speed (Sanders 2005).